(untitled) (Theatrum historiae, 2012)
František Křižík is one of the few technicians in the Czech history who is perceived as a national hero. This study deals with the notion of his personality as a “capitalistic entrepreneur” as interpreted by Marxistic society in the fifties of the 20th century.